2008
DOI: 10.1016/j.amc.2007.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A two-parameter defect-correction method for computation of steady-state viscoelastic fluid flow

Abstract: The numerical simulation of viscoelastic fluid flow becomes more difficult as a physical parameter, the Weissenberg number, increases. Specifically, at a Weissenberg number larger than a critical value, the iterative nonlinear solver fails to converge. In this paper a two-parameter defect-correction method for viscoelastic fluid flow is presented and analyzed. In the defect step the Weissenberg number is artificially reduced to solve a stable nonlinear problem. The approximation is then improved in the correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The numbers of steps and steplength reductions required for each method for computations with a = 1 on mesh M1 are reported in Table 5 temporally unsteady solutions) exist beyond some critical value of λ. The same observation was also made during numerical experiments with a defect-correction method for viscoelasticity [16]. Trebotich, et al [45] also observed this situation and suggested that the wave-like behavior is related to the elastic Mach number.…”
Section: High Weissenberg Number Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…The numbers of steps and steplength reductions required for each method for computations with a = 1 on mesh M1 are reported in Table 5 temporally unsteady solutions) exist beyond some critical value of λ. The same observation was also made during numerical experiments with a defect-correction method for viscoelasticity [16]. Trebotich, et al [45] also observed this situation and suggested that the wave-like behavior is related to the elastic Mach number.…”
Section: High Weissenberg Number Resultsmentioning
confidence: 63%
“…The defect-correction method has been applied to steady-state viscoelastic flows [17,16,32] for high Weissenberg number. In their approach, the defect step consisted of a nonlinear iteration in which the Weissenberg number was replaced with an artificially reduced value, and the correction step sought to improve on the approximation found in the defect step.…”
Section: Continuation In Weissenberg Numbermentioning
confidence: 99%
“…Due to its good efficiency, there are many works devoted to this method, e.g. the convection-diffusion equation, [24] adaptive refinement for the convection-diffusion problems, [25] adaptive defect-correction methods for the viscous incompressible flow, [26] two-parameter defect-correction method for computation of the steady-state viscoelastic fluid flow, [27] variational methods for the elliptic boundary value problems, [28] defect-correction parameter-uniform numerical method for a singularly perturbed convection-diffusion problem, [29] the convection-dominated flow, [30] finite volume local defect-correction method for solving the transport equation, [31] the singular initial value problems, [32] the time-dependent Navier-Stokes equations, [33][34][35] the stationary Navier-Stokes equation, [36] second-order defect-correction scheme, [37] finite element eigenvalues with applications to quantum chemistry, [38] and so on. In [28], a method which makes it possible to apply the idea of iterated defect correction to finite element methods was given.…”
Section: Introductionmentioning
confidence: 99%
“…Because it is highly efficient, there are many works devoted to this method, e.g. the convection-diffusion equation [17], adaptive refinement for the convection-diffusion problems [2], adaptive defect correction methods for the viscous incompressible flow [18], two-parameter defectcorrection method for computation of the steady-state viscoelastic fluid flow [20], variational methods for the elliptic boundary value problems [21], defectcorrection parameter-uniform numerical method for a singularly perturbed convection-diffusion problem [28], the convection-dominated flow [33], finite volume local defect correction method for solving the transport equation [34], the singular initial value problems [35], the time-dependent Navier-Stokes equations [36,37,41], the stationary Navier-Stokes equation [39], second order defect correction scheme [42], finite element eigenvalues with applications to quantum chemistry [46] and so on. In [21], Frank et al give a method which makes it possible to apply the idea of iterated defect-correction to finite element methods.…”
Section: Introductionmentioning
confidence: 99%